Effect of Hepatitis B Virus Infection on Sperm Quality and Outcomes of Assisted Reproductive Techniques in Infertile Males - Wang, Zichun; Liu, Wanpeng; Zhang, Mingming; Wang, Minglei; Wu, Huaying; Lu, Meisong (Frontiers in Medicine, 2021)
Background: Hepatitis B virus (HBV) infection is one of the health problems and has adverse effects on public health. However, the consequences of male HBV carriers for assisted reproductive techniques (ART) remain unclear. Objective: To examine whether men with HBV would impact sperm quality and the intrauterine insemination (IUI)/ in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI) outcomes. Methods: We retrospectively analyzed data from 681 infertile couples for IUI/IVF/ICSI fresh cycle outcomes. Case group was 176 infertile couples with male HBV infection undergoing embryo transfer in our center (99 for IVF and 77 for ICSI) and 51 infertile couples for IUI. Negative control was 454 non-infected infertility couples, matched for female age, BMI and infertility duration (102 for IUI and 198 for IVF and 154 for ICSI). Results: Sperm viability among infertile men with HBV infection was significantly lower than control group (74.1±13.7 vs. 77.0±12.8, P<0.01). Sperm motility was significantly decreased in HBV positive men in comparison to the control group (32.5±14.6 vs. 35.5±12.9, P<0.05). In IVF/ICSI cycles, two groups had similar results in two pronuclear (2PN) fertilization rate, implantation rate, clinical pregnant rate and abortion rate (P>0.05). There was also no difference in the clinical pregnant rate and abortion rate in IUI cycles (P>0.05). Conclusion: Men with HBV infection will affect their sperm quality, but not affect the outcomes of ART.